2016
DOI: 10.1108/ics-03-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repeated data breach events on organisations’ market value

Abstract: Purpose -In this study, we examined the influence of one or more information security breaches on an organization's stock market value as a way to benchmark the wider economic impact of such events. Design/Methodology/approach -We used an event studies based approach where a measure of the event's economic impact can be constructed using security prices observed over a relatively short period of time. Findings -Based on the results, we argue that although no strong conclusions could be made given the current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Yet there is virtually no study that uses actual customer transaction data and empirically examines the effect of a DBA on customer behavior. Although a few studies have examined the impact of security breaches on firm value (e.g., Schatz and Bashroush 2016), no study has examined the impact of a DBA on customer behavior. We attempt to fill this gap in the literature.…”
mentioning
confidence: 99%
“…Yet there is virtually no study that uses actual customer transaction data and empirically examines the effect of a DBA on customer behavior. Although a few studies have examined the impact of security breaches on firm value (e.g., Schatz and Bashroush 2016), no study has examined the impact of a DBA on customer behavior. We attempt to fill this gap in the literature.…”
mentioning
confidence: 99%
“…A large number of studies deal with information security breaches and cyber security (Schatz and Bashroush, 2016), but there is still a limited amount of literature related to the tourism and hospitality sector on this field. Nevertheless, specialized literature on the tourism industry emphasizes that the ICT strategy may have a direct impact on the financial performance of a hotel (Tavitiyaman et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But, competitiveness measurement is a complex activity (Crouch & Ritchie, 1999). There have been efforts to measure it in previous studies either with the help of financial measures (Barrett, Davidson, Prabhu, & Vargo, 2015;Krell & Matook, 2009;Prescott, 2014;Sigalas, Economou, & Georgopoulos, 2013) or non financial measure such as creative process of product/service development, Product/service quality, customer responsiveness reflected through customer retention/attraction, cost saving/effectiveness, market differentiation, strategic planning, core competence, and social responsibility (Agha, Alrubaiee, & Jamhour, 2012;Al-alak & Tarabieh, 2011;Barrett et al, 2015;Diab, 2014;Epetimehin, 2011;Heywood & Kenley, 2008;Kuettner & Schubert, 2012;Majeed, 2011;Matikiti, Afolabi, & Smith, 2012;Prescott, 2014;Schatz & Bashroush, 2016;Sigalas et al, 2013;Vahid et al, 2013;Kasasbeh, Harada, & Noor, 2017), which need to be identified in the specific context for better understanding to the researchers and practitioners, in future.…”
Section: Competitivenessmentioning
confidence: 99%